(untitled) - Zuffoletto, Joe (Indianapolis, IN, 2003)
* A comprehensive, hands-on guide to the nuts and bolts of installing, administering, and troubleshooting the latest version of WebLogic Server ; * Extensive coverage of building enterprise applications with this popular J2EE application server ; * Updated edition includes new coverage of BEA's WebLogic Workshop tool with WebLogic Server, expanded coverage of security and clustering, WebLogic Integration, and WebLogic Portal ; * BEA leads the J2EE application server market, and its market share continues to grow ; * Companion Web site features additional code, examples, and updates.
Keywords: Web servers,Application software,Phần mềm ứng dụng,Web máy chủ